Effect of planting systems, seed rates and nitrogen levels con bread wheat (Triticum aestivum)* - KUMAR, RAJESH; AGGARWAL, S K; NANWAL, R K (The Indian Journal of Agricultural Sciences, 2011)
Of the two methods of sowing, viz bed planting and conventional sowing did not had their significant effect on yield components and grain yield. Spikes/m, grains/spike and grain yield of wheat was significantly higher with bed planting at 75 kg over 50 kg/ha seed and was at par with 100 kg/ha seed. These parameters with 120 kg N/ha under bed planting were at par with conventional method of sowing at 150 kg Nka. The study indicate that ’PBW 343’ bread wheat can be sown at 75 kg/ha seed with 120 kg N/ha under bed planting system for getting sustainable yield.